PROPAGATION AND ARTIFICIAL SEEDS PRODUCTION FROM SINGLE NODE EXPLANTS OF MACLURA THAT CULTURED IN VITRO - M. T. Al-Jubori; M. A. Al-Shamari (The Iraqi Journal of Agricultural science)
In this study, an ideal protocol for the in vitro propagation of Maclura plants was established. The effect of using sodium alginate at different concentrations on the production of artificial seeds from single nodes was investigated. The results showed that the Maclura plant can be successfully propagated in vitro by culturing single nodes on Woody Plant Medium (WPM) with 0.6mg /L GA3, resulting in a percentage response of up to 100%. The highest average number and length of shoots was achieved at this concentration with 5 shoots/explant and 1.31 cm, respectively. At the multiplication stage, the treatment with 0.5mg/L BA + 0.1mg/L NAA) was superior, resulting in the highest average number of shoots of 5.50 shoots/explant. At the rooting stage, the use of IBA at 3mg/L was best and resulted in the highest average number of roots (5.60 roots/shoot). The survival rate of 100% was achieved when soil and pitmoss were used in a 1:1 ratio after the seedlings had been transferred to the field for two months. The results of the artificial seed experiment showed that the interaction between 2% sodium alginate + 15 g/L calcium chloride achieved the highest percentage of survival, 80% after one month of cold storage at 4c◦.